I becomes we, but where is me? The unity–division paradox when caring for a relative with dementia: A qualitative study. (29th July 2019) - Tierney, Stephanie; Tutton, Elizabeth; Seers, Kate
Abstract: Background: The number of older people living with dementia is increasing. Admiral Nurses work with these individuals and their families in the UK to manage challenges associated with the condition, providing guidance, advice and reassurance, alongside practical solutions. Aim: To explore the input of Admiral Nurses as part of people's journey to becoming and being a carer for someone with dementia. Design: A qualitative study was conducted to describe and understand how Admiral Nurses are experienced and encountered by carers as part of their narrative around supporting a relative with dementia. Methods: Semi‐structured interviews were conducted with 19 carers between November 2017–April 2018. They lasted between 45 and 90 min. Thematic analysis was used to interpret data. Findings: An overarching concept of "the unity–division paradox" was derived from the data. This highlights the complex interchange between the carer with (a) the person with dementia, (b) other individuals and (c) external services. Such interactions can make carers feel part of a larger network (unity) but also as if they are on their own, fighting on behalf of the person with dementia (division). This concept was underpinned by the following themes: (a) I becomes we; (b) My private world is encroached by dementia; (c) I'm left navigating an unwieldy system; (d) Are you with or against us?; and (e) Recreating boundaries to rediscover me. Conclusion: The identity and unique characteristics and interests of those caring for a person with dementia may be lost as they encounter tensions associated with the unity–division paradox. Admiral Nurses can help carers feel less alone in managing internal and external struggles by supporting them to do their best for a loved one with dementia. Implications for practice: Understanding carers' experience and supporting their work may help to increase and sustain their capacity to provide care.